(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
In the modern world, cars have become an integral part of human life. They play an important role in transportation, economic activity, and everyday life. However, the rapid growth of the number of cars is causing serious harm to the environment. In Uzbekistan, especially in the last decade, the number of cars has increased significantly. For example, according to UzAutoMotors, in 2023, more than 1.5 million cars were registered in the country, which is 40% more than in 2015. This article analyzes the impact of the increasing number of cars on nature, considers the situation in Uzbekistan, and makes proposals to mitigate the problem.